Inflation Targeting Is a Success, So Far: 100 Years of Evidence from Swedish Wage Contracts - Klas Fregert; Lars Jonung (Kiel Institute for the World Economy (IfW), 2008)
Inflation targeting was adopted by several countries, including Sweden, in the 1990s. We evaluate the Swedish inflation targeting regime since 1995 using a novel approach based on a unique data set on the characteristics of collective wage agreements between 1908 and 2008. First, we establish that the length of wage contracts decreases in response to an increase in ?macroeconomic uncertainty? across policy regimes. Second, using contract length as the assessment criteria for regime performance, we find that the inflation targeting regime of 1995?2008 stands out as an exceptionally stable policy regime as judged by the willingness of wage contract-makers to repeatedly commit to three-year non-indexed wage agreements. In addition, inflation targeting gained instant credibility in the sense that the labor market organizations entered long-term wage agreements at the same time as this new regime was announced. Inflation targeting has thus reduced macroeconomic uncertainty compared to previous regimes adopted in Sweden during the 20th century. Our approach to evaluate inflation targeting is different from the traditional one commonly based on cross-section samples comparing inflation outcomes. Instead we focus on the actual decisions of private-sector wage setters under different monetary regimes. Judging from their behavior across a century of observations, inflation targeting in Sweden is a success – at least so far.
Keywords: E42; E30; E65; 330; Inflation targeting; policy regime; contract length; wage indexation; Lucas critique; Sweden; credibility; Inflation Targeting; Wirtschaftspolitische Wirkungsanalyse; Lohnbildung; Tarifpolitik; Lohnindexierung; Schweden